A secondary battery
By using low oil absorption conductive agent in the negative electrode sheet of lithium-ion battery and high oil absorption conductive agent in the positive electrode sheet, the problem of insufficient rate performance and cycle life of lithium-ion battery is solved, and higher power performance and longer cycle life are achieved.
Patent Information
- Application Number
- CN202211594204.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The existing lithium-ion batteries have shortcomings in terms of rate performance and cycle life. The main reasons are the poor conductivity of the positive electrode materials, poor electronic conductivity, poor liquid retention, and poor ion conductivity between the electrolyte and the material, resulting in poor kinetic performance.
Use conductive agents with low oil absorption and low graphitization degree in the negative electrode sheet to improve conductivity and liquid retention; use conductive agents with high oil absorption and high graphitization degree in the positive electrode sheet to enhance ionic conduction and electron conduction between the positive electrode materials and reduce impedance.
The high-rate performance and long cycle life of lithium-ion batteries are achieved, reducing costs, and improving the battery's power and cycle performance.
Smart Images

Figure GDA0004203665790000071 
Figure GDA0004203665790000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a secondary battery. Background Art
[0002] Lithium-ion batteries have outstanding advantages such as high energy density, high operating voltage, low self-discharge rate, and environmental friendliness, and can be used as ideal batteries for motors. Compared with ordinary lithium-ion batteries for electric vehicles, batteries need to continuously pursue high power and long cycle life. The battery rate performance obtained by the existing technical methods is low and the high-temperature cycle is poor. The main reasons are that the positive electrode material has poor conductivity, poor electronic conductivity, poor liquid retention, poor ion conduction between the electrolyte and the material, and large ion resistance, which leads to poor kinetic performance. On the other hand, the conductive agent is not easy to disperse evenly in the negative electrode water system, resulting in poor electronic conductivity between materials and thus poor kinetic performance. Therefore, a method is needed to solve the above technical problems. Summary of the invention
[0003] One of the purposes of the present invention is to provide a secondary battery in view of the shortcomings of the prior art, in which a conductive agent with low oil absorption and low graphitization degree is used in a negative electrode sheet with good liquid retention and high conductivity to reduce costs; a positive electrode conductive agent with high oil absorption and high graphitization degree is used in a positive electrode sheet with poor liquid retention and low conductivity to increase ion conduction and electron conduction between positive electrode materials, reduce impedance, and thus obtain a battery with excellent power performance and cycle performance.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A secondary battery comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating disposed on at least one surface of the positive electrode current collector, wherein the positive electrode coating comprises a positive electrode conductive agent, wherein the specific surface area of the positive electrode conductive agent is 55 to 90 m 2 / g, the structural oil absorption value of the positive electrode conductive agent is 250-400ml / 100g, the negative electrode sheet includes a negative electrode current collector and a negative electrode coating disposed on at least one surface of the negative electrode current collector, the negative electrode coating includes a negative electrode conductive agent, and the specific surface area of the negative electrode conductive agent is 55-90m 2 / g, and the structural oil absorption value of the negative electrode conductive agent is 150-250ml / 100g.
[0006] Preferably, the weight fraction of the positive electrode conductor in the positive electrode coating is 1.0% to 6.0%.
[0007] Preferably, the Raman spectrum ID / IG ratio of the positive electrode conductive agent is 0.9 to 1.3.
[0008] Preferably, the weight fraction of the negative electrode conductive agent in the negative electrode coating is 0.5% to 3.0%.
[0009] Preferably, the Raman spectrum ID / IG ratio of the negative electrode conductive agent is 1.3 to 1.8.
[0010] Preferably, the positive electrode coating also includes a positive electrode active material, which includes at least one or more of a nickel cobalt manganese oxide ternary material that has been modified with or without doping coating, a lithium iron phosphate material that has been modified with or without carbon coating, a lithium iron manganese phosphate material, a lithium manganese oxide material, and a lithium cobalt oxide material.
[0011] Preferably, the chemical formula of the nickel-cobalt-lithium-manganese oxide ternary material is Li x Ni a Co b Mn c O2, of which 0.85 <x<1.2,0≤a≤1,0≤b≤1,0≤c≤1,a+b+c=1。
[0012] Preferably, the chemical formula of the lithium manganese iron phosphate material is Li x Mn a Fe b PO4, of which 0.85 <x<1.2,0≤a≤1,0≤b≤1,a+b=1。
[0013] Preferably, the positive electrode conductive agent is at least one of natural carbon, carbon black, carbon nanotubes, graphite, soft carbon, hard carbon, amorphous carbon, etc. and / or the negative electrode conductive agent is at least one of natural carbon, carbon black, carbon nanotubes, graphite, soft carbon, hard carbon, amorphous carbon, etc.
[0014] Preferably, the negative electrode coating further includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon element, silicon oxide, and tin element.
[0015] Preferably, the positive electrode coating further includes a binder, and the negative electrode coating further includes a binder, and the binder includes one of styrene-butadiene rubber, polyacrylamide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, and polyimide.
[0016] Compared with the prior art, the beneficial effects of the present invention are: a secondary battery of the present invention has higher rate performance and longer cycle life. The lithium-ion battery of the present invention uses a conductive agent with low oil absorption and low graphitization in the negative electrode sheet with good liquid retention and high conductivity to reduce costs. A positive electrode conductive agent with high oil absorption and high graphitization is used in the positive electrode sheet with poor liquid retention and low conductivity to increase ion conduction and electron conduction between positive electrode materials, reduce impedance, and thus obtain a battery with excellent power performance and cycle performance. DETAILED DESCRIPTION
[0017] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.
[0018] A secondary battery comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating arranged on the positive electrode current collector, the positive electrode coating comprises a positive electrode conductive agent, and the specific surface area of the positive electrode conductive agent is 55 to 90 m 2 / g, the structural oil absorption value of the positive electrode conductive agent is 250-400ml / 100g, the negative electrode sheet includes a negative electrode current collector and a negative electrode coating arranged on the negative electrode current collector, the negative electrode coating includes a negative electrode conductive agent, and the specific surface area of the negative electrode conductive agent is 55-90m 2 / g, and the structural oil absorption value of the negative electrode conductive agent is 150-250ml / 100g.
[0019] Since lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphorus oxide and lithium iron manganese phosphorus oxide, which are used as positive electrode materials of lithium-ion batteries, have low conductivity and poor liquid absorption capacity, the internal resistance of the entire electrode increases, the utilization rate of active materials is low, and when the charge and discharge current increases, the polarization increases, and the battery cycle life decreases. In order to ensure that the battery electrode has good charge and discharge performance, a certain amount of conductive agents such as furnace black, acetylene black and carbon nanotubes are usually added when making the positive electrode plate to increase the conductivity between the active material and the current collector and between the active material particles and the electrolyte absorption capacity of the plate, thereby improving the electronic conductivity and ionic conductivity of the battery and improving the charge and discharge efficiency. For negative electrode materials such as graphite and natural graphite, although they have certain conductivity and liquid absorption capacity, when the battery is charged and discharged at a high rate, the gaps between the graphite particles reduce the rate performance of the battery. Therefore, conductive carbon black, acetylene black and other conductive agents with smaller particles (before adding the electrode slurry, the particle diameter is usually 40-400 nanometers) are added to the electrode slurry when making the electrode. It is hoped that these conductive carbon black, acetylene black and other conductive agents with smaller particles can collect microcurrents between graphite particles and between graphite and the current collector, reduce the contact resistance of the electrode, and accelerate the migration rate of electrons, so as to effectively improve the migration rate of lithium ions in the electrode material and increase the conductivity of the electrode.
[0020] When making pole pieces, the active material, conductive agent, binder and solvent are mixed in proportion, and the evenly mixed electrode slurry is loaded on the positive and negative current collectors. After drying, rolling and cutting, the positive and negative pole pieces are obtained. The pole pieces and the isolation film are then wound to form a core. The core is wrapped with aluminum-plastic film to form a semi-finished battery cell, and then the electrolyte is injected. After the formation and capacity separation steps, the finished lithium-ion battery is obtained, and the electrical performance is tested.
[0021] In actual production applications, it was found that the ionic conductivity and electronic conductivity of the battery cell are both important factors affecting the rate performance of the battery cell. Analysis shows that the reason may be that the positive electrode has poor liquid absorption capacity and poor conductivity. Lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphorus oxide and lithium iron manganese phosphorus oxide, which are the positive electrode materials of lithium-ion batteries, have low conductivity and poor liquid absorption capacity. This increases the internal resistance of the entire electrode and the utilization rate of the active material is low. When the charge and discharge current increases, the polarization increases and the battery cycle life is reduced.
[0022] Therefore, the purpose of the present invention is to overcome the shortcomings of poor rate performance and poor cycle performance in the prior art, and a secondary battery of the present invention has higher rate performance and longer cycle life. The lithium-ion battery of the present invention uses a conductive agent with low oil absorption and low graphitization in the negative electrode sheet with good liquid retention and high conductivity to reduce costs. A positive electrode conductive agent with high oil absorption and high graphitization is used in the positive electrode sheet with poor liquid retention and low conductivity to increase ion conduction and electronic conduction between positive electrode materials, reduce impedance, and thus obtain a battery with excellent power performance and cycle performance.
[0023] In order to achieve the reasonable application of conductive agents, we need to select suitable positive and negative conductive agent materials. Among them, the conductive carbon used can be at least one of activated carbon, carbon black, carbon nanotubes, graphite, soft carbon, hard carbon, amorphous carbon, etc.; the positive electrode conductive agent can be selected from a specific surface area of 55-90㎡ / g, an oil absorption value of 250-400ml / 100g, and Raman: ID / IG 0.9-1.3; the negative electrode conductive carbon black can be selected from a specific surface area of 55-90㎡ / g, a structural oil absorption value of 150-250ml / 100g, and a Raman: ID / IG 1.3-1.8.
[0024] The positive and negative electrode sheets and the separator are wound to form a core and assembled into a semi-finished battery. After the electrolyte is injected, the lithium-ion battery is obtained through the processes of formation and capacity separation. Compared with the design outside the scope, it has better dynamic performance and high cycle life.
[0025] In some embodiments, the weight fraction of the positive electrode conductive agent in the positive electrode coating is 1.0% to 6.0%. Preferably, the weight fraction of the positive electrode conductive agent in the positive electrode coating is 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, or 6.0%.
[0026] In some embodiments, the Raman spectrum ID / IG ratio of the positive electrode conductive agent is 0.9 to 1.3. Preferably, the Raman spectrum ID / IG ratio of the positive electrode conductive agent is 0.9, 1.0, 1.1, 1.2, or 1.3.
[0027] In some embodiments, the weight fraction of the negative electrode conductive agent in the negative electrode coating is 0.5% to 3.0%. Preferably, the weight fraction of the negative electrode conductive agent in the negative electrode coating is 0.5%, 0.8%, 1.1%, 1.3%, 1.5%, 1.8%, 2.0%, 2.4%, 2.8%, 3.0%.
[0028] In some embodiments, the Raman spectrum ID / IG ratio of the negative electrode conductive agent is 1.3 to 1.8. Preferably, the Raman spectrum ID / IG ratio of the negative electrode conductive agent is 1.3, 1.4, 1.5, 1.6, 1.7, or 1.8.
[0029] In some embodiments, the positive electrode coating also includes a positive electrode active material, which includes at least one or more of a nickel cobalt manganese oxide ternary material that has been modified with or without doping coating, a lithium iron phosphate material that has been modified with or without carbon coating, a lithium iron manganese phosphate material, a lithium manganese oxide material, and a lithium cobalt oxide material.
[0030] In some embodiments, the chemical formula of the nickel-cobalt-lithium-manganese oxide ternary material is Li x Ni a Co b Mn c O2, of which 0.85 <x<1.2,0≤a≤1,0≤b≤1,0≤c≤1,a+b+c=1。
[0031] In some embodiments, the negative electrode coating further includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon, silicon oxide, and tin.
[0032] In some embodiments, the positive electrode coating further includes a binder, and the negative electrode coating further includes a binder, and the binder includes one of styrene-butadiene rubber, polyacrylamide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, and polyimide.
[0033] A secondary battery of the present invention has a positive electrode that uses a positive electrode conductive agent with a certain specific surface area and a large structural oil absorption value, so that the positive electrode has a certain liquid absorption and retention ability, better wettability, and improved ion conductivity. The negative electrode uses a negative electrode conductive agent with a certain specific surface area and a low structural oil absorption value to reduce costs. The secondary battery prepared by the positive electrode sheet and the negative electrode sheet working together has higher rate performance and longer cycle life.
[0034] According to the physical properties of conductive carbon, conductive carbon is divided into conductive carbon 1 to 6, and the properties are listed in Table 1.
[0035] Table 1
[0036]
[0037] Example 1
[0038] The positive electrode material powder, conductive carbon, carbon nanotubes and PVDF were mixed in a specified ratio, and then NMP was added in a high-speed mixer and uniformly mixed into a slurry with a solid content of 74%. The slurry was coated on one side of an aluminum foil with a thickness of 13 microns using a transfer coater and dried to maintain a unit area coating weight of 20.0 mg / cm2 after drying. Then the same process was used to coat and dry the other side of the aluminum foil to obtain a semi-finished positive electrode sheet.
[0039] Artificial graphite powder, conductive carbon, carbon nanotubes, CMC and SBR were mixed in a specified ratio, and then deionized water was added in a high-speed mixer and evenly mixed into a slurry with a solid content of 48%. The slurry was applied to one side of a copper foil with a thickness of 8 microns using a transfer coater and dried to maintain a unit area coating weight of 18.1 mg / cm2 after drying. The same process was then used to coat and dry the other side of the copper foil to obtain a negative electrode semi-finished product.
[0040] The exposed metal foil of the pole piece is processed and welded into a pole ear, and then wound with a separator to form a winding core. The winding core is wrapped with an aluminum-plastic film to form a semi-finished battery cell, and then the electrolyte is injected with an injection coefficient of 4g / Ah. After the formation and capacity separation steps, the finished lithium-ion battery is obtained.
[0041] Slurry performance test
[0042] 1. Slurry fineness test
[0043] The QXD scraper fineness meter of Tianjin Jingke Material Testing Machine was used to test the fineness of the positive electrode slurry according to GB / T1 724-89. The smaller the slurry fineness, the better the dispersion of the particulate material in the slurry.
[0044] 2. Slurry rheological properties test
[0045] The rheological properties of the positive electrode slurry were tested using Anton Paar's Physica MCR 301 rotational rheometer according to the American Society for Testing and Materials standard ASTM D 7175-2005. The rheological properties test of the slurry can show the fluidity.
[0046] Pole performance test
[0047] 1. Positive electrode sheet resistivity test
[0048] The ACCFilm film resistor is used to directly measure the overall resistivity of the electrode. The resistance measured at this time includes the resistance of the probe itself, the contact resistance between the probe and the coating, the coating resistance, the contact resistance between the coating and the current collector, and the resistance of the current collector itself. During the measurement process, the main parameters include the loading current and the pressure applied by the probe. The corresponding test standard is GB / T 19587-2017. The test principle is Ohm's theorem: R=U / I. If the conductive agent is unevenly dispersed in the dispersant and forms larger agglomerates, the conductive agent on the electrode electrode sheet thus made will also be unevenly dispersed, resulting in less or no conductive agent in the local area, thereby increasing the resistivity of the electrode sheet. Therefore, the smaller the resistivity, the more evenly the conductive agent is dispersed on the electrode sheet.
[0049] Battery performance test
[0050] 1. Liquid retention coefficient
[0051] The battery filling coefficient is 4g / Ah. With the same filling volume, some electrolyte will be lost after the formation and the second seal. The actual electrolyte retention coefficient is the value of the actual electrolyte mass retained in the final battery divided by the actual battery capacity. The larger the battery retention coefficient, the more electrolyte the electrode absorbs, and the required amount of electrolyte injection can be relatively reduced, which reduces costs. The electrode has good liquid absorption ability and relatively low ionic resistance, which has advantages in rate performance.
[0052] 2. IMP
[0053] After the battery is prepared and divided into capacities, it is placed for 48 hours and then the impedance is tested using a DC resistance instrument.
[0054] 3. EIS
[0055] The CHI660 chemical workstation was used to perform AC impedance testing on lithium batteries with a test frequency of 0.03Hz-100kHz, and the Zview software was used to fit and analyze the AC impedance spectrum of the test.
[0056] 4. Rate performance
[0057] First, test the 1C capacity. Place the lithium-ion battery in a constant temperature environment of 25°C for 1h, use the nominal capacity for 1C / 1C charging and discharging, charge at a constant current of 1C to a voltage of 4.3V, then charge at a constant voltage of 4.3V with a cut-off current of 0.05C. After standing for 15 minutes, discharge at a constant current of 1C to 2.8V, and the discharge capacity is the 1C capacity C0; 4C rate test: charge at a constant current of 1C0 to a voltage of 4.3V, then charge at a constant voltage of 4.3V with a cut-off current of 0.05C. After standing for 15 minutes, discharge at a constant current of 4C0 to 2.8V, and the discharge capacity is C1.
[0058] Cycle performance
[0059] 3. 45 degree 3C / 3C cycle performance test:
[0060] First, in an environment of 45°C, the first charge and discharge were carried out. After constant current charging at a charging current of 1C to a voltage of 4.3V, the charging cut-off current was 0.05C at a constant voltage of 4.3V. After standing for 15 minutes, constant current discharge was carried out at a discharge current of 1C to 2.8V. The discharge capacity of the first cycle was recorded as C1; then charge and discharge cycles were carried out until the capacity decayed to 80% C1 ended, and the number of cycles corresponding to the discharge capacity retention rate of 80% was recorded.
[0061] 4. Cyclic DCR and DCR growth test:
[0062] After the first cycle of 45 degree cycle in 3 is charged to 4.3V with 1C1 constant current, the charging cut-off current is 0.05C0 at 4.3V constant voltage. After standing for 15 minutes, the voltage V3 is one second before the discharge starts. The voltage V4 is recorded after 30s of 1C0 constant current discharge. The first cycle (capacity maintained 100%) discharge DCR1 is (V3-V4) / C1. The same test obtains DCR2 after the cycle capacity decays by 80%, and the cycle DCR growth is (DCR2-DCR1) / DCR1×100%.
[0063] Prepare Examples 2-10 with reference to Example 1, and record the corresponding performance test results in Table 2.
[0064] Table 2
[0065]
[0066] It can be concluded from Table 2 above that when both the positive electrode and the negative electrode use conductive carbon with low surface oxygen content, such as in Examples 1, 4, and 6, the prepared battery positive electrode has good performance, but the negative electrode has poor performance, resulting in poor overall battery performance, a liquid retention coefficient between 3.74 and 3.78, a low overall capacity between 107 and 118, and a capacity retention rate between 550 and 603. When both the positive electrode and the negative electrode use conductive carbon with low graphitization, such as in Examples 2, 7, and 9, the prepared battery positive electrode has poor performance, an electrode resistance between 2.82 and 3.09, and poor overall battery performance. When the capacity retention rate is reduced to 80%, the number of charge and discharge cycles is 507 to 542. When a conductive carbon with a low surface oxygen content is used for the positive electrode and a conductive carbon with a high surface oxygen content is used for the negative electrode when preparing the battery, such as in Examples 3, 5, 8, and 10, the prepared battery has better performance. A charge and discharge cycle test was carried out at 45 degrees Celsius with a 2C charge rate / 2C discharge rate. After 912 cycles of charge and discharge, the battery still had a capacity retention rate of 80%.
[0067] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A secondary battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating arranged on the positive electrode current collector, wherein the positive electrode coating comprises a positive electrode conductive agent, and the specific surface area of the positive electrode conductive agent is 55 to 90 m 2 / g, the oil absorption value of the positive electrode conductive agent is 250-400 ml / 100 g, the negative electrode sheet comprises a negative electrode current collector and a negative electrode coating arranged on the surface of the negative electrode current collector, the negative electrode coating comprises a negative electrode conductive agent, and the specific surface area of the negative electrode conductive agent is 55-90 m 2 / g, the oil absorption value of the negative electrode conductive agent is 150~250ml / 100g; the Raman spectrum ID / IG ratio of the positive electrode conductive agent is 0.9~1.3; the Raman spectrum ID / IG ratio of the negative electrode conductive agent is 1.3~1.
8.
2. The secondary battery according to claim 1, characterized in that: The weight fraction of the positive electrode conductive agent in the positive electrode coating is 1.0% to 6.0%.
3. The secondary battery according to claim 1, characterized in that: The weight fraction of the negative electrode conductive agent in the negative electrode coating is 0.5% to 3.0%.
4. The secondary battery according to claim 1, characterized in that: The positive electrode coating also includes a positive electrode active material, which includes at least one or more of a nickel cobalt manganese oxide ternary material that has been or has not been modified by doping or coating, a lithium iron phosphate material that has been or has not been carbon-coated, a lithium iron manganese phosphate material, a lithium manganese oxide material, and a lithium cobalt oxide material.
5. The secondary battery according to claim 1, characterized in that: Both the positive electrode conductive agent and the negative electrode conductive agent include carbon black.
6. The secondary battery according to claim 5, characterized in that: The positive electrode conductive agent and the negative electrode conductive agent further include at least one of activated carbon, carbon nanotubes, graphite, soft carbon, hard carbon, and amorphous carbon.
7. The secondary battery according to claim 4, characterized in that: The chemical formula of the nickel-cobalt-lithium-manganese oxide ternary material is Li x Ni a Co b Mn c O2, of which 0.85 <x<1.2,0≤a≤1,0≤b≤1,0≤c≤1,a+b+c=1。 8. The secondary battery according to claim 1, characterized in that: The negative electrode coating also includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon, silicon oxide, and tin.
Citation Information
Patent Citations
Active material for secondary batteries, secondary battery, and electronic device
CN103988347A
Lithium ion secondary cell
CN104247135A
Conductive carbons for lithium ion batteries
CN105308775A
All-solid lithium secondary battery, manufacturing method thereof, method of use thereof, and charging method thereof
CN111755741A
Preparation method of positive electrode slurry, positive electrode plate and lithium ion battery
CN114284465A